P258 Bloodstream infections caused by serratia marcescens in paediatric patients. (6th June 2017) - Erat, Tuğba; Yahši, Aysun; Kara, Tuğ;çe Tural; Özdemir, Halil; Azapağasi, Ebru; Perk, Oktay; Kendirli, Tanil; Ince, Elif Ünal; Atasay, Begüm; Ünal, Emel; Çiftçi, Ergin; Ince, Erdal
Abstract : We reported a retrospective cohort study was designed to investigate features of S. marcescens outbreak in a children hospital, Turkey. S. marcescens was isolated from the blood culture of 45 patient. Their demographic and clinical features, results of antimicrobial susceptibility testing and 28 day all cause mortality were recorded. The most common underlying condition was malignancy (26.9%). The median length of hospital stay was 42, 7±41.4 (3–171) days. Forty-three of the patients had CVCs during the BSI episodes. Primary BSI was diagnosed in 24 (53.3%) episodes, catheter related BSI were considered in 21 episodes. The median duration of CVC prior to catheter related BSI 46, 02±50, 96 (1-200) days. 24 catheter (55.8%) was removed. Four patients (8.9%) died during the bacteriemia episode. Fatal group laboratory findings; median WBC, median serum CRP and albumin level were higher than non-fatal group. 57.8% isolates of S. marcescens produced ESBL and 40% isolates produced carbapenemases. We classified this isolates non-MDR (42.2%), MDR (31.1%), XDR (24.4%) and PDR (2.2%). The most common regimes received for XDR isolates were meropenem infusion, amikacin, levofloxacin and tigecycline. Since S. marcescens isolates are intrinsically resistant to polymyxins, and producting ESBL, carbapenemase among these pathogens is a cause of great concern. Mortality reduced by continuous-infusion meropenem and removed catheters early.